Urological Society of Australia and New Zealand (USANZ) and Australasian Chapter of Sexual Health Medicine (AChSHM) for the Royal Australasian College of Physicians (RACP) clinical guidelines on the management of erectile dysfunction. Issue 6 (4th September 2022) - Chung, Eric; Lowy, Michael; Gillman, Michael; Love, Chris; Katz, Darren; Neilsen, Graham
Abstract: Introduction: These clinical practice recommendations by the Urological Society of Australia and New Zealand (USANZ) and the Australasian Chapter of Sexual Health Medicine (AChSHM) for the Royal Australasian College of Physicians (RACP) provide evidence‐based clinical guidelines on the management of erectile dysfunction (ED) in Australia. Main recommendations: A comprehensive clinical history and a tailored physical examination are essential (Level of evidence [LoE] 3; GRADE B). Laboratory testing should include fasting glucose, lipid profile and total testosterone level (LoE 3; GRADE A). Specialised diagnostic tests are recommended in selected cases and the patient should be counselled accordingly (LoE 4; GRADE B). Lifestyle changes and optimisation of existing medical conditions should accompany all ED treatment regimens (LoE 1; GRADE A). Oral phosphodiesterase type 5 inhibitor (PDE5i) is an effective first line medical therapy (LoE 1; GRADE A). Intracavernosal injections and vacuum erection devices are recommended as second line therapy (LoE 1; GRADE B). A penile prosthesis implant can be considered in men who are medically refractory or unable to tolerate the side effects of medical therapy (LoE 4; GRADE B). Pro‐erectile regenerative therapy remains largely experimental (LoE 3; GRADE B). Changes in management as a result of these guidelines: Modification of lifestyle behaviour, management of reversible risk factors and optimisation of existing medical conditions remain pivotal, and existing standard ED therapies are often effective and safe following cardiovascular risk stratification. Caution should be exercised on the use of regenerative technology in ED due to unknown long term outcomes.